KAJIAN HISTORIS TENTANG MODEL ISTINBATH AL AHKAM PADA MASA AWAL ISLAM - Achmad Achmad (IAIN Syekh Nurjati Cirebon, 2022)
This study aims to discuss and review the model of using the ijtihad method that has been used by the early Islamic generation, especially the companions. Although scientifically the standard model of ijtihad only emerged in the second century of Hijriyah, especially after Imam Syafii wrote Arrisalah, in fact historically it turned out that long before that, the products of ijtihad which were the result of the thoughts of the Companions, became known as ijtihad. Friend. From the results of the research, it turns out that the friend's Ijtihad method, both when the Prophet was still alive and after his death was already developed, at least the ijtihad method embryo was born.The method used in this study is descriptive analysis method, the approach is using qualitative methods. Because this research is related to the study of the method of thinking of the characters (friends) of the past, this research is included in historical research. In collecting data, this research fully uses library research.From the results of this study it was found that since the beginning of Islam the istinbath al ahkam model and the ijtihad method have been formed, which was initiated by the generation of companions. The majority of scholars agree on this, but they differ on what method the Companions used in their ijtihad